2007
DOI: 10.1093/rheumatology/kem063
|View full text |Cite
|
Sign up to set email alerts
|

The TNF superfamily member LIGHT contributes to survival and activation of synovial fibroblasts in rheumatoid arthritis

Abstract: The results provide evidence for a novel T-cell-dependent activation of synovial fibroblasts by LIGHT in joints of patients with RA, contributing to an inflammatory and destructive phenotype.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
47
2
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(57 citation statements)
references
References 34 publications
7
47
2
1
Order By: Relevance
“…However, the lack of efficacy of HVEM-Ig in the late phase of disease might also stem from opposing effects of HVEM-Ig on adaptive immunity. Adaptive immunity might still be contributing to this chronic stadium, and inhibiton of this system might outweigh the effect of direct inhibition of the proinflammatory effects, which LIGHT exerts on human rheumatoid arthritis synoviocytes (33). Our study expands data from two previous manuscripts published with opposing results (15,16), which used LT␤R-Ig in the chronic phase of CIA with no conlusive evidence for a pro-or antiinflammatory role for the investigated molecules LIGHT and LT␣1␤2.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…However, the lack of efficacy of HVEM-Ig in the late phase of disease might also stem from opposing effects of HVEM-Ig on adaptive immunity. Adaptive immunity might still be contributing to this chronic stadium, and inhibiton of this system might outweigh the effect of direct inhibition of the proinflammatory effects, which LIGHT exerts on human rheumatoid arthritis synoviocytes (33). Our study expands data from two previous manuscripts published with opposing results (15,16), which used LT␤R-Ig in the chronic phase of CIA with no conlusive evidence for a pro-or antiinflammatory role for the investigated molecules LIGHT and LT␣1␤2.…”
Section: Discussionsupporting
confidence: 50%
“…LIGHT is up-regulated in the joints of patients with rheumatoid arthritis and mediates proinflammatory effects on joint-resident cells as macrophages (32) and fibroblasts (33). The rational for blocking LIGHT in mice with established joint inflammation was to investigate a phase of the disease in which adaptive immune responses are of minor importance, and to test whether the disease is still influenced.…”
Section: Discussionmentioning
confidence: 99%
“…This finding contrasts with numerous previous studies in a wide variety of cell types that have reported that LIGHT, acting via either HVEM or LT␤R, activates NF-B (Marsters et al, 1997;Hikichi et al, 2001;Matsui et al, 2002;Zou and Hu, 2005;Wei et al, 2006;Pierer et al, 2007). We have previously shown that NF-B is a key regulator of neurite growth in neonatal nodose neurons, and that inhibiting canonical NF-B signaling in these neurons significantly reduces BDNF-promoted neurite growth during a developmental window from E18 to P1 (Gutierrez et al, Figure 6.…”
contrasting
confidence: 86%
“…Although a decoy receptor for LIGHT, DcR3, has been described in humans, the existence of a mouse homolog has not been described and is considered unlikely (Gommerman and Browning, 2003;Bossen et al, 2006). LIGHT has multiple functions in the immune system and has been implicated in the regulation of cell proliferation and survival in several tissues and organs (Ware, 2005;Murphy et al, 2006;Pierer et al, 2007), but has no known role in the nervous system. HVEM and LT␤R lack death domains and interact with adaptors of the TRAF family to modulate several signaling pathways including the NF-B transcription family (Grivennikov et al, 2006), which has been implicated in regulating neurite growth from neonatal nodose ganglion neurons (Gutierrez et al, 2005;Gallagher et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…25 Also known as herpes virus entry mediator for its role as a herpes virus receptor, TNFRSF14 is expressed on the surface of T cells and synovial fibroblasts and activates the canonical nuclear factor-kB (NF-kB) pathway upon ligation of LIGHT, a TNF super family member. [26][27][28] TRAF1-C5 was previously reported to be associated with RA in primarily Caucasian populations. 29 The OR for association with the minor allele of the rs3761847 SNP was reported at 1.32, which is comparable to an OR of 1.23 we report in the NAN population, using the same SNP.…”
Section: Discussionmentioning
confidence: 98%